Oscar Wilde, Wilfred Owen, and Male Desire - Campbell, James. author. aut Link
X, 241 p.
Keywords: This book reads Oscar Wilde as a queer theorist and Wilfred Owen as his symbolic son. It centers on the concept of 'male procreation', or the generation of new ideas through an erotic but non-physical connection between two men, and it sees Owen as both a product and a continuation of this Wildean tradition.